Starch based bioplastic from sweet potato with plasticizer and filler / Muhammad Faren Mohd Kamal - Mohd Kamal, Muhammad Faren (2023)
One of the many workable alternatives to polymers made from petrochemical industries is the use of bioplastics. Bioplastics have several advantages over conventional plastics, including a lower carbon footprint, increased energy efficiency, increased biodegradability, and increased adaptability. In this study, sweet potato starch-based bioplastic was made using the casting method along with plasticizer and filler. Box-Behnken Design analysis was used to determine the best way to prepare the bioplastics for water absorption. The sweet potato was used to extract the starch. Wood dust is used as a filler, and sorbitol and glycerol are used as plasticizers. Investigations were made into physical characteristics such as content moisture. The bioplastic was weighed initially, dried in an oven for three hours at 35C, and then weighed once more for the final weight. The final optimization calculation for content moisture is: content moisture = +5.8911764705882 + 1.41375 starch + 20.94375 filler + 0.989025 plasticizer + 6.8625 starch * filler + 0.053125 starch * plasticizer + 7.359375 filler * plasticizer. The minimum percentage is 7.58%. Starch-based substances have enormous potential for use as biodegradable plastics, which will help to protect the environment. Continued research into this bioplastic is necessary.